The Investigation of Hyaluronidase Activity in Muscle of Medicine Leech (Hirudo medicinalis) - Şahin, Ayşe Gül; Sağlam, Naim (Fırat University, 2016)
The aim study, it was determined the level of hyaluronidase that having a broad range of applications in medicine and pharmacology. Therefore the level and monthly changes of hyaluronidase were spectrophotometrically investigated in the muscle of medicine leech (Hirudo medicinalis) reared in Cip Fish Reproduction Unit of Fırat University Fisheries Faculty. During the study, the muscle samples from both anterior and posterior parts of total 168 of leeches were dissected and then they were extracted for determination of hyaluronidase levels. While the highest hyaluronidase level was found as 1692.69±40.65µmol/L (1190.49- 2270.07) in march, the lowest hyaluronidase activites was found as 322.98±13.41 µmol/L (207.31-824.21) in september. In conclusion, it was determined that the monthly changes of hyaluronidase level in the muscle of medicine leech (Hirudo medicinalis) were found statistically significant (P ? 0.05). As a result after hibernation, gathered leeches are more appropriate than the other periods as did in point of obtaining hyaluronidase from H. medicinalis.

Çalışmanın amacı tıpta ve farmakolojide geniş bir kullanım alanına sahip olan hyaluronidazın seviyesini belirlemektir. Bu nedenle,Fırat Üniversitesi Su Ürünleri Fakültesi Cip Balık Üretim ve Araştırma tesisindeki sülük üretim ve yetiştirme havuzlarında yetiştirilen Tıbbi sülük Hirudo medicinalis’in kas dokusunda hyaluronidaz aktivitesi ve aylara göre değişimi spektrofotometrik yöntemle araştırıldı. Çalışmada, bir yıl boyunca toplam 168 adet sülüğün anteriör ve posteriör bölgelerindeki kas dokularının ekstraksiyonu yapılarak belirtilen dokularda hyaluronidaz miktarı saptandı. En yüksek hyaluronidaz aktivitesi Mart ayında ortalama 1692,69±40,65 µmol/L (1190,49 – 2270,07), en düşük hyaluronidaz aktivitesi ise eylül ayında 322,98±13,41 µmol/L (207,31– 824,21) olduğu tespit edildi. Tıbbi sülük H. medicinalis’in kas dokusundaki hyaluronidaz aktivitelerinin aylara göre dağılımları arasındaki farkın istatistiksel olarak önemli olduğu (p ? 0,05) belirlendi. Sonuç olarak, Hirudo medicinalis’ten hyaluronidazın elde edilmesi düşünüldüğünde kış uykusundan çıkan sülüklerin toplanarak değerlendirilmesi hyaluronidazın elde edilmesi açısından uygun olacaktır.
Hirudo medicinalis (Tıbbi Sülük)’in Kas Dokusunda Hyaluronidaz Aktivitesinin Araştırılması